1993
DOI: 10.1007/bf00202476
|View full text |Cite
|
Sign up to set email alerts
|

Detection of complete and partial chromosome gains and losses by comparative genomic in situ hybridization

Abstract: Abstract. Comparative genomic in situ hybridization (CGH)provides a new possibility for searching genomes for imbalanced genetic material. Labeled genomic test DNA, prepared from clinical or tumor specimens, is mixed with differently labeled control DNA prepared from cells with normal chromosome complements. The mixed probe is used for chromosomal in situ suppression (CISS) hybridization to normal metaphase spreads (CGH-metaphase spreads). Hybridized test and control DNA sequences are detected via different fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
309
0
11

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 523 publications
(322 citation statements)
references
References 30 publications
2
309
0
11
Order By: Relevance
“…CGH analysis was carried out as described previously with minor modifications. 15 Briefly, biotin-labeled tumour DNA and digoxigenin-labeled reference DNA (Roche Diagnostics, Mannheim, Germany) were precipitated in the presence of Cot-1 DNA (Invitrogen, Karlsruhe, Germany) and salmon sperm DNA (Sigma, Munich, Germany) and hybridized for 3 days to normal metaphase spreads of a healthy donor. Probe detection was carried out using FITC for biotin-and Cy3 for digoxigenin-labeled DNA probes, respectively.…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
“…CGH analysis was carried out as described previously with minor modifications. 15 Briefly, biotin-labeled tumour DNA and digoxigenin-labeled reference DNA (Roche Diagnostics, Mannheim, Germany) were precipitated in the presence of Cot-1 DNA (Invitrogen, Karlsruhe, Germany) and salmon sperm DNA (Sigma, Munich, Germany) and hybridized for 3 days to normal metaphase spreads of a healthy donor. Probe detection was carried out using FITC for biotin-and Cy3 for digoxigenin-labeled DNA probes, respectively.…”
Section: Comparative Genomic Hybridizationmentioning
confidence: 99%
“…CGH analysis was performed according to Kallioniemi et al (1992) and du Manoir et al (1993) with modifcations. 600 ng of biotin-16-dUTP labelled DNA and 600 ng of SpectrumRed direct-labelled normal male DNA were simultaneously hybridized with 25 µg unlabelled Cot-1 DNA (Life Technologies Inc, Grand Island, NY) to denatured lymphocyte metaphases for 3 days.…”
Section: Cgh and Image Analysismentioning
confidence: 99%
“…No chromosomal aberrations specific to phyllodes tumors have been identified so far. Using comparative genomic hybridization (CGH), a technique that allows a genome-wide screening of chromosome imbalances in a single experiment, 15,16 recurrent gains and losses, þ 1q, À3p, þ 7q, À6q and À3q, were found in phyllodes tumors. 17 Other molecular studies showed that somatic or germinal mutations of TP53 were present in isolated cases of malignant phyllodes tumors.…”
mentioning
confidence: 99%